2008
DOI: 10.1002/jmr.919
|View full text |Cite
|
Sign up to set email alerts
|

The titanium binding protein of Rhodococcus ruber GIN1 (NCIMB 40340) is a cell‐surface homolog of the cytosolic enzyme dihydrolipoamide dehydrogenase

Abstract: Rhodococcus ruber GIN1 (formally Rh. strain GIN1) was previously isolated on the basis of its strong adherence to coal fly ash (CFA) and titanium dioxide particles from CFA sedimentation ponds of an electrical power plant in Israel. The interaction of the bacterium with oxides has been shown to be mediated by a cell surface protein designated TiBP (titanium binding protein) involving primarily strong, non-electrostatic forces. In this work, we set forward to identify this unique exocellular protein. Sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…However, it was shown previously that DLDH is not involved in metabolising 2-oxo acids in the Pneumococcus, indicating that DLDH may serve other functions (Smith et al, 2002), which is supported by evidence that organisms that lack 2-oxo acid dehydrogenases still express a DLDH protein (Danson, 1988). Siegmann et al (2009) identified DLDH in Rhodococcus ruber as an exocellular protein involved in binding titanium dioxide particles by nonelectrostatic forces.…”
Section: Proteome Comparison Of Streptomycetes Grown On Glass Vs Zirmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it was shown previously that DLDH is not involved in metabolising 2-oxo acids in the Pneumococcus, indicating that DLDH may serve other functions (Smith et al, 2002), which is supported by evidence that organisms that lack 2-oxo acid dehydrogenases still express a DLDH protein (Danson, 1988). Siegmann et al (2009) identified DLDH in Rhodococcus ruber as an exocellular protein involved in binding titanium dioxide particles by nonelectrostatic forces.…”
Section: Proteome Comparison Of Streptomycetes Grown On Glass Vs Zirmentioning
confidence: 83%
“…Siegmann et al . () identified DLDH in Rhodococcus ruber as an exocellular protein involved in binding titanium dioxide particles by nonelectrostatic forces.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, DLDH forms an exceptionally strong interaction with TiO 2. This interaction is based on a specific binding site and involves coordinative bonding via CHED residues …”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was calculated that about 2000 protein molecules (equivalent to 8000 RGD moieties) were bound per μm 2 . The strong binding of DLDH to TiO 2 was shown to be dissociated only in the presence of high molar concentrations of urea …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation